Characteristics and predictors of treatment effectiveness of children seen at the Therapeutic Learning Centre, Division of Child and Adolescent Psychiatry, Red Cross War Memorial Children's Hospital during the period 1992-2008 - Dhansay, Yumna (Division of Child and Adolescent Psychiatry, 2014)
Includes abstract. Includes bibliographical references.